PENINGKTAN MOTIVASI BELAJAR SISWA DENGAN MENGGUNAKAN METODE DEMONSTRASI PADA MATA PELAJARAN KETERAMPILAN SULAMAN TRADISIONAL DI KELAS VII 1 SMPN 18 PADANG - Yuhelmi, Dra. Ernis, M.Pd, Drs. Syafril R, M.Sn (Serupa The Journal of Art Education, 2013)
The purposes of this research was to state the improving students’ motivation in learning transfer a sketch of embroidery into paper and cloth in VII grade of SMPN 18 Padang with using demonstration method in individual learning process. The data was collected using observation to see the change of students’ learning activities in 2 cycles that were cycle I and cycle II. This research involved 31 students that consist of 14 femalestudents and 18 male students. The data got and analyzed with percentage technique. Research findings indicate that improving in positive activities, students who asked question improve 24%, students who finished task improve 32%, students who finished task seriously improve 11%, and workteam improve 6%. Findings also indicate that reducing in negative activities, students who walked out class reduce 10%, students who made voices reduce 13%, students who not made task reduce 7%, students who not brought material reduce 7%, and students who always disturb others reduce 3%. In addition, students’ result in learning improving, in cycle I 70% of students completed the text and cycle II 84% of students completed the test. It can be concluded that demonstration method in arts class can improve students’ motivation in VII grade SMPN 18 Padang. Key words: Motivasi Belajar Siswa, Metode Demonstrasi, PelajaranKeterampilan Sulaman Tradisional Kelas VII 1 SMPN 18Padang